Analisis Aplikasi Akad Tabarru’ dalam Asuransi Syariah: Studi Kasus pada AJB Bumiputera 1912 Syariah Cabang Kudus - Hakim, M. Arif (IAIN Salatiga, 2012)
The purpose of this research is to (1) know of products of Islamic insurance at AJB Bumiputera 1912 Syariah Cabang Kudus; (2) know how procedure and mechanism of application of akad tabarru’ in Islamic insurance at AJBBumiputera 1912 Syariah Cabang Kudus; (3) analyse the application of akadtabarru’ in Islamic insurance at AJB Bumiputera 1912 Syariah CabangKudus.This research including field research with qualitative approach. Dataanalysis using descriptive analysis.Result of this research indicate that (1)products at AJB Bumiputera 1912 Syariah Cabang Kudus are products withsaving system; individual insurance (Mitra Sakinah, Mitra Mabrur and MitraIqra’) and group insurance; (2) in executing daily activity of AJB Bumiputera1912 Syariah Cabang Kudus, premium which step into the company groupedto become the Tabarru’ (benefaction fund), Premium of Saving and Premiumof Cost; (3) application of Akad tabarru’ at AJB Bumiputera 1912 SyariahCabang Kudus as according to religious advices of Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) No. 21/DSN-MUI/X/2001 about common guidance of islamic insurance expressed that akad tabarru’ is all form akad done with benefaction purpose and help mutually, not for the commercial purpose